Heterogeneity and Environmental Preferences Shape the Evolution of Cooperation in Supply Networks. (20th April 2021) - Mu, Dong; Yue, Xiongping
Abstract : Supply networks as complex systems are significant challenges for decision-makers in predicting the evolution of cooperation among firms. The impact of environmental heterogeneity on firms is critical. Environment-based preference selection plays a pivotal role in clarifying the existence and maintenance of cooperation in supply networks. This paper explores the implication of the heterogeneity of environment and environment-based preference on the evolution of cooperation in supply networks. Cellular automata are considered to examine the synchronized evolution of cooperation and defection across supply networks. The Prisoner's Dilemma Game and Snowdrift Game reward schemes have been formed, and the heterogeneous environment and environmental preference have been applied. The results show that the heterogeneous environment's degree leads to higher cooperation for both Prisoner's Dilemma Game and Snowdrift Game. We also probe into the impact of the environmental preference on the evolution of cooperation, and the results of which confirm the usefulness of preference of environment. This work offers a valuable perspective to improve the level of cooperation among firms and understand the evolution of cooperation in supply networks.